Pengaruh Disiplin Kerja, Kompensasi, Dan Lingkungan Kerja Terhadap Kinerja Karyawankantor Kecamatan Sidoarjo [The Influence Of Work Discipline, Compensation, And Work Environment On Employee Performance In The Sidoarjo District Office] - Bachrudin; Mukhamat Ali; Sumartik (International Journal on Human-Computing Studies, 2021)
This study aims to determine the effect of work discipline, compensation, and work environment on employee performance in the Sidoarjo sub-district office This research is quantitative research with hypothesis testing. The sample used in this study were 54 employees in the Sidoarjo subdistrict office. The analytical tool used in this research is multiple linear regression analysis using SPSS version 18 for windows. The primary data in this study were obtained from a questionnaire whose measurements used a Likert scale that was tested for validity and reliability. The results of this study prove that work discipline has an effect on employee performance, Compensation has an effect on employee performance, the work environment also has an effect on employee performance, in addition to that work discipline, compensation and work environment have an effect simultaneously on employee performance.